The HR2 Haplotype of Factor V: Effects on Factor V Levels, Normalized Activated Protein C Sensitivity Ratios and the Risk of Venous Thrombosis - de Visser, Marieke C. H.; Guasch, Joan F.; Kamphuisen, Pieter W.; Vos, Hans L.; Rosendaal, Frits R.; Bertina, Rogier M. (Thrombosis and Haemostasis, 2000)
We studied the HR2 haplotype of the factor V gene in a case-control study for venous thrombosis including 474 patients with a first deep-vein thrombosis and 474 age- and sex-matched healthy controls (Leiden Thrombophilia Study, LETS). We investigated both the original His1299Arg (A4070G) polymorphism and the Met385Thr (T1328C) polymorphism. This latter polymorphism, located in exon 8 (heavy chain), is always present in the HR2 haplotype, but also occurs on its own in a His1299 (wt) background. The HR2 haplotype was not associated with an increased risk of venous thrombosis (OR = 1.2, 95% confidence interval: 0.8-2.0). We did not find an association between the HR2 haplotype and a reduced sensitivity for activated protein C (APC) in non-carriers of factor V Leiden (FVL). However, in compound heterozygous FVL/HR2 carriers the sensitivity for APC was reduced. The HR2 haplotype was also associated with reduced factor V antigen levels in both patients and controls. Sequence analysis of the promoter region of factor V in HR2 homozygotes did not reveal any sequence variations that could explain the reduced FV levels. Our results show that the HR2 haplotype is not associated with an increased risk of venous thrombosis or with a reduced sensitivity for APC in non-FVL carriers. However, the HR2 haplotype is associated with a reduced sensitivity for APC in carriers of FVL and with reduced factor V antigen levels.
Keywords: HR2 haplotype; factor V; APC resistance; venous thrombosis